Where and When Bacterial Chromosome Replication Starts: A Single Cell Perspective - Trojanowski, Damian; Hołówka, Joanna; Zakrzewska-Czerwińska, Jolanta (Frontiers in Microbiology, 2018)
Bacterial chromosomes have a single, unique replication origin (named oriC), from which DNA synthesis starts. This study describes methods of visualizing oriC regions and the chromosome replication in single living bacterial cells in real-time. This review also discusses the impact of live cell imaging techniques on understanding of chromosome replication dynamics, particularly at the initiation step, in different species of bacteria.